Approximate Solution of Multi-Term Fractional Order Delay Differential Equations Using Homotopy Perturbation Method - S. Ismael, Mohammed; S. Fadhel, Fadhel; Al-Fayadh, Ali (Al-Nahrain Journal of Science, 2020)
In this paper the approximate solution of the non-linear equations of multi-term fractional order delay differential equations by using the homotopy perturbation method is considered. The fractional order derivative is communicated in the Caputo sense. In this methodology, the solutions are found in the form of a convergent power series with easily computed components. Finally, some examples are given to illustrate the obtained results, and then a comparison between the exact and the approximate results were given and they are presented in order to show the reliability and the accuracy of the proposed method.